Effects of Touch on Students’ Stress, Happiness, and Well-Being During Animal-Assisted Activities (Journal of Education and Development, 2021)
Post-secondary institutions across North America have adopted animal-assisted activities as a way to promote better mental health in their students. The current research study of 242 Canadian college and university students sought to contribute to our collective understanding of the aspects of the programs and characteristics of students that are related to promotion of better mental health in post-secondary students including decreased stress, and increased happiness and well-being. Results of a repeated measures design showed that students demonstrated greater positive effects on stress, happiness, and well-being when they touched dogs as compared to when they observed them. Furthermore, positive mental health outcomes were correlated with greater durations of contact as well as with higher levels of animal affiliation in students. Implications for post-secondary institutions are discussed.